2011
DOI: 10.1080/01926187.2010.539479
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Family Coordination in Divorced Families

Abstract: The principal aim of this study is to adapt the standardized observational method of family relationships-the Lausanne Trilogue Play (LTP; Fivaz-Depeursinge & Corboz-Warnery, 1999)-to typical observed clinical situations. Our objective is to assess if this procedure is useful in distinguishing and standardizing the levels of complexity of those divorced families who are being followed by a court expert in child custody cases. Sixty high-conflict divorced families participated in this research project. The fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The LTP paradigm (Fivaz-Depeursinge and Corboz-Warnery, 1999) was modified to be applied to adolescents up to 18 years (Malagoli Togliatti and Mazzoni, 2006; Lavadera et al, 2011) The coding scheme of the LTP (Malagoli Togliatti and Mazzoni, 2006) used herein was adopted and explained in other international works (Lavadera et al, 2011; Mazzoni and Lubrano Lavadera, 2013; Mazzoni et al, 2015). Fivaz-Depeursinge supervised the modifications of the task and the coding system proposed and manualized by Malagoli Togliatti and Mazzoni (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LTP paradigm (Fivaz-Depeursinge and Corboz-Warnery, 1999) was modified to be applied to adolescents up to 18 years (Malagoli Togliatti and Mazzoni, 2006; Lavadera et al, 2011) The coding scheme of the LTP (Malagoli Togliatti and Mazzoni, 2006) used herein was adopted and explained in other international works (Lavadera et al, 2011; Mazzoni and Lubrano Lavadera, 2013; Mazzoni et al, 2015). Fivaz-Depeursinge supervised the modifications of the task and the coding system proposed and manualized by Malagoli Togliatti and Mazzoni (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the increasing number of studies using this innovative observational tool in different family contexts (Frascarolo et al, 2005; Lavadera et al, 2011; Simonelli et al, 2012; Mazzoni et al, 2015), data regarding families with adolescent offspring are still very limited. Nevertheless a recent study (Gatta et al, 2016b), aiming to examine the usefulness of the LTP as an outcome measure, found that the LTP assessment of the family interactions might help clinicians to focus on the dysfunctional familial dynamics, thus improving the effectiveness of a video-feedback intervention with the families of children and adolescents with psychiatric disorders (i.e., significantly reducing internalizing symptoms).…”
Section: Introductionmentioning
confidence: 99%
“…The LTPc coding system used in this study has been explained in previous publications (14,52,54,55). Essentially, it considers four aspects of interaction (i.e., participation, organization, focal attention, affective contact), which are rated, in each phase, on a three-point Likert scale (0 = dysfunctional; 1 = partially functional; 2 = functional).…”
Section: The Ltpc: Procedures and Codingmentioning
confidence: 99%
“…In a related study, Lavadera, Laghi, and Togliatti ( 2011 ) developed an observational method of family relationships and interactions-the Lausanne trilogue play (LTP)-and adapted it to typical observed clinical situations. The major objective of their study was to assess whether this procedure is useful in distinguishing among the levels of complexity and characteristics of divorced families who are being followed by a court expert in child custody cases.…”
Section: Alliancementioning
confidence: 99%